Pengaruh Perceived Quality dan Perceived Sacrifice Terhadap Perceived Value serta Dampaknya Pada Customer Loyalty di PT XYZ - Wahyudi, Triyono Arief (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2020)
This study aims to analyze the influence of perceived quality and perceived sacrifice on perceived value and its impact on customer loyalty at PT Haldin Pacific Semesta, particularly in the Spice and Seasoning Ingredients Division. A quantitative method was applied using a survey of 111 loyal customers who have partnered with the company for more than two years. The sample was selected through purposive sampling based on specific criteria. Data were collected via questionnaires tested for validity and reliability, then analyzed using classical assumption tests, Pearson correlation, coefficient of determination, path analysis, and t-tests. The findings indicate that both perceived quality and perceived sacrifice have a positive and significant effect on perceived value, while perceived value positively and significantly influences customer loyalty. Moreover, perceived quality and perceived sacrifice indirectly affect customer loyalty.